Ipomoea kahloiae (Convolvulaceae), a noteworthy new species endemic to Guerrero, Mexico - González-Martínez, César Adrián; Lozada-Pérez, Lucio; Rios-Carrasco, Sandra; Alvarado-Cárdenas, Leonardo O.; Martínez-González, César Ramiro; Castro-Lara, José Manuel; Jiménez-Ramírez, Jaime (Phytotaxa, 2018)
A new species of Ipomoea, I. kahloiae, is described and illustrated. It is endemic to tropical semideciduous forests in the Acahuizotla area of the Sierra Madre del Sur in Guerrero, Mexico. Information about its distribution, ecology, conservation and morphology is provided. Phylograms are presented to clarify the relationships of this new species within Ipomoea.